The Sedimentary Geochemical Characteristics and Geological Significance of the Wufeng-Longmaxi Formation Accumulation of Organic Matter Black Shale on the Southeastern Sichuan Basin, China. (7th July 2022) - Wu, Bin
Abstract : At present, the understanding of the sedimentary paleoenvironment and organic matter enrichment law of black shale in the Wufeng-Longmaxi Formation is still insufficient. This time, we investigated the total organic carbon (TOC) content, X-ray diffraction mineralogical composition, and the major and trace element abundances of the newly recovered cores of three shale gas exploration wells in Changning, Qianjiang, and Xiushan areas which were, respectively, selected to discuss and compare the varying paleoenvironmental conditions and the factors that control organic matter accumulation, such as terrigenous input, redox conditions, primary productivity, and the degree of water retention in the basin. The results show that black siliceous shale lithofacies, gray-black shale lithofacies, gray-black silty shale lithofacies, gray argillaceous siltstone lithofacies, and gray shell marl lithofacies are mainly deposited in the Wufeng-Longmaxi Formation in the southeastern Sichuan Basin. Organic-rich black shale is mainly concentrated in the lower part of the Wufeng Formation and Longmaxi Formation. The continuous thickness of organic carbon content greater than 2% in the Changning area is 32 m, the continuous thickness in the Qianjiang area is 22 m, and the continuous thickness in the Xiushan area is 11 m. The hydrocarbon generation potential gradually weakens from west to east. The identification of the geochemical behavior characteristics of major and trace elements shows that enrichment of the organic matter black shale section in the Changning-Qianjiang-Xiushan areas is mainly formation in the anoxic-moderate water mass restriction environment with high primary productivity and less terrigenous detritus input under the low hydrodynamic conditions. However, the correlations of terrigenous detrital proxies Ti/Al, redox proxies V/Cr, Ni/Co, and paleoproductivity proxies Babio with the TOC contents show that the Changning area is a favorable area for the formation of organic-rich black shale and the Qianjiang area is affected by the Wuling underwater uplift; the thickness of the black shale deposits becomes thinner; the Xiushan area is adjacent to the Xuefeng uplift, and the deposition conditions of the accumulation of organic matter black shale deteriorate, which is unfavorable for shale gas exploration.